Impact of Carbon Dioxide Pneumoperitoneum on Liver Function Tests in Laparoscopic Cholecystectomy, A Prospective Study - Nazir, Muhammad Shahbaz; Nawaz, Maria; Awan, Afzal Saeed; Nawaz, Hafiza Ayesha; Iqbal, Laiba; Irfan, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the impact of carbon dioxide pneumoperitoneum on liver function tests in patients undergoing laparoscopic cholecystectomy for a benign disease as an elective surgery.Study Design: Prospective longitudinal study.Place and Duration of Study: Army Liver Transplant Unit, Pak Emirates Military Hospital Rawalpindi, Pakistan from Mar 2021 to Feb 2024.Methodology: The study included 455 patients who underwent elective laparoscopic cholecystectomy in a tertiary care hospital in accordance with the inclusion and exclusion criteria. All patients of 18-80 years of age with normal LFTs were included and those with liver and associated diseases that could affect the LFTs were excluded. The detailed medical history and laboratory findings were recorded preoperatively and post operatively on the 1st, 3rd, and 7th post operative day and evaluated for any significant change in values.Results: ALP and LDH showed a rise in serum values after surgery. The mean values before surgery for ALP and LDH were 88.09±30.19 U/L and 201.11±42.46 U/L respectively. After seven days of surgery, the mean values of ALP and LDH were 91.69±32.86 U/L and 212.16±44.31 U/L respectively with p-value